Why Atherosclerotic Vessels Narrow: The Fibrin Hypothesis - Yee, Karen O.; Schwartz, Stephen M. (Thrombosis and Haemostasis, 1999)
Conventional wisdom holds that atherosclerosis narrows vessels simply by growth of the plaque.1 We now know, however, that this is incorrect. Morphological studies from the last 10 years have shown that there is no correlation between lesion size and lumen diameter. This lack of correlation is also true in the lesions found in the apolipoprotein E (apoE)-deficient mouse model.2 Pathologic studies in the mouse model and in humans suggest that the media remodels as the plaque enlarges to maintain normal blood flow through the vessel.3,4 This normal ability of the vessel to adapt to changes in lumen diameter has been called either “adaptive remodeling” or “compensatory enlargement.” We will use the former term since “remodeling” has long been used by physiologists to describe adaptive changes of vessels to pressure or flow.The mechanism for adaptive remodeling is not known. Critical processes may include shear stress caused by the lesion, signaling in response to medial attenuation by proteases, or poorly defined apoptotic processes.3-5 This chapter will review the evidence for adaptive remodeling and propose a mechanism for the ultimate failure of remodeling and subsequent narrowing of the affected vessel. We will suggest that the critical processes in vascular narrowing are the same processes seen in wound healing, with fibrin playing a role as a provisional matrix.